UJI DAYA ANTIBAKTERI BAWANG PUTIH (Allium sativum L.) TERHADAP BAKTERI Staphylococcus aureus, Escherichia coli, Salmonella typhimurium DAN Pseudomonas aeruginosa DALAM MENINGKATKAN KEAMANAN PANGAN - Prihandani, Sri Suryatmiati (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2015)
Garlic is widely used as a herbal medicine. In order to support the empirical use and improve its application in food safety, this study was conducted to test the antibacterial activity of garlic against Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli, Salmonella typhimurium and Pseudomonas aeruginosa) bacteria. Garlic was used in the form of fine powder. Garlic powder then dissolved in sterile distilled water and squeezed to obtain garlic solution with a concentration of 50%, 25% and 12.5%. Antibacterial activity of garlic juice was tested by diffusion method using paper disc to determine diameter of bacterial growth inhibition zones. Screening results demonstrated that the chemical constituents of garlic powder were saponins, flavonoids and triterpenoids. Garlic powder has antibacterial activity to Gram-positive S. aureus and Gram-negative bacteria E. coli, S. typhimurium and P. aeruginosa. Garlic has antimicrobial potential and can be used as decontaminant against Escherichia coli to maintain quality of food safety such as meat.